Nü Jidu in Matthew 24:27: An exegetical evaluation of Dongfang Shandian in China - Harman Z. Laia; Jimmy Sutrisno (HTS Teologiese Studies/Theological Studies)
This study examined the text of Matthew 24:27 using the exegetical method, which included textual, contextual, grammatical-structural, lexical and theological analysis. The purpose of this research was to evaluate and critique the interpretation put forth by the Eastern Lightning group, which claims that Christ has returned to the world as a Chinese woman through a second incarnation based on this text. However, the analysis revealed that the verse does not prophesy Christ’s second coming; rather, it depicts the nature of that coming, likening it to lightning flashing from the east to the west. This coming will be public, universal, clear, evident and witnessed by all humanity. Christ’s return has not yet occurred, but it will happen at the end of time, preceded by various terrifying events around the world known as the tribulation. Christ will return in his male form, as he ascended to heaven, not as a woman, and in his glory as King, not in the humble state of a human, to judge all humanity living on earth.